Society in Public Service: Challenges Service Recording Marriage in Indonesia - Purba, Della Agnesia; Ramadhan, Adityo Pratikno; Marianata, Anita (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
Marriage registration is a fundamental legal process that ensures the protection of marital rights and administrative recognition. However, many married couples have yet to obtain official marriage certificates, particularly in Bengkulu City, Indonesia. This study aims to identify the factors influencing community participation in marriage registration. Using a descriptive qualitative research method, this research explores societal attitudes and administrative challenges associated with the registration process. Data was collected through in-depth interviews, observations, and document analysis involving key informants, including married couples, religious figures, and government officials. A content analysis technique was employed to interpret the findings systematically. The results indicate that low public awareness and limited legal knowledge are the primary factors contributing to the reluctance to register marriages with the civil registry. Many couples believe that religious marriage alone is sufficient and are unaware of the legal consequences of unregistered marriages, such as complications in inheritance, child legitimacy, and access to state services. Additionally, a lack of government-led awareness campaigns and inadequate public outreach efforts have exacerbated the issue, leaving many couples uninformed about the registration process and its legal significance. This study highlights the urgent need for enhanced legal literacy, targeted socialization efforts, and administrative reforms to improve marriage registration rates. Strengthening collaboration between government agencies, religious institutions, and community organizations is crucial to increasing public participation. These findings contribute to the broader discourse on public administration and legal compliance in non-Western governance systems, emphasizing the role of community-driven legal awareness in enhancing civic engagement. Further research is recommended to explore marriage registration challenges across different socio-economic and cultural backgrounds to develop more inclusive and effective policy interventions.